A mutant fibrinogen that is unable to form fibrin can improve renal phenotype in mice with sickle cell anemia. Issue 3 (15th June 2021) - Narciso, Marilou G.; Hoeting, Blair; James, Jeanne M.; VandenHeuvel, Katherine; Nasimuzzaman, Md.
Abstract: Sickle cell anemia (SCA) causes nephropathy which may progress to kidney failure. To determine if soluble fibrinogen (Fib AEK ) can prevent kidney damage in mice with SCA, we performed bone marrow transplantation (BMT) of Berkeley sickle mice into wild‐type fibrinogen (Fib WT ), and Fib AEK mice that bear a germ‐line mutation in fibrinogen Aα chain at thrombin cleavage site which prevents fibrin formation. We found improved albuminuria in SS Fib AEK mice compared with SS Fib WT mice at 12 months post‐BMT due to the reduced kidney fibrosis, ischemic lesions, and increased survival of podocytes in the glomeruli, but did not improve urine concentrating defect. Therefore, our study clarifies the distinct role of fibrinogen and fibrin in the renal pathology of SCA.